Lung cancer in HIV patients and their parents: A Danish cohort study - Engsig, Frederik N (BioMed Central, 2011)
BACKGROUND: HIV patients are known to be at increased risk of lung cancer but the risk factors behind this are unclear. METHODS: We estimated the cumulative incidence and relative risk of lung cancer in 1) a population of all Danish HIV patients identified from the Danish HIV Cohort Study (n = 5,053) and a cohort of population controls matched on age and gender (n = 50,530) (study period; 1995 - 2009) and 2) their parents (study period; 1969 - 2009). Mortality and relative risk of death after a diagnosis of lung cancer was estimated in both populations. RESULTS: 29 (0.6%) HIV patients vs. 183 (0.4%) population controls were diagnosed with lung cancer in the observation period. HIV patients had an increased risk of lung cancer (adjusted incidence rate ratio (IRR); 2.38 (95% CI; 1.61 - 3.53)). The IRR was considerably increased in HIV patients who were smokers or former smokers (adjusted IRR; 4.06 (95% CI; 2.66 - 6.21)), male HIV patients with heterosexual route of infection (adjusted IRR; 4.19 (2.20 - 7.96)) and HIV patients with immunosuppression (adjusted IRR; 3.25 (2.01 - 5.24)). Both fathers and mothers of HIV patients had an increased risk of lung cancer (adjusted IRR for fathers; 1.31 (95% CI: 1.09 - 1.58), adjusted IRR for mothers 1.35 (95% CI: 1.07 - 1.70)). Mortality after lung cancer diagnose was increased in HIV patients (adjusted mortality rate ratio 2.33 (95%CI; 1.51 - 3.61), but not in the parents. All HIV patients diagnosed with lung cancer were smokers or former smokers. CONCLUSION: The risk was especially increased in HIV patients who were smokers or former smokers, heterosexually infected men or immunosuppressed. HIV appears to be a marker of behavioural or family related risk factors that affect the incidence of lung cancer in HIV patients.